Information Technology Implementation (Digitalization) on Booking and Payment Online System to Village's Tourism Product in Bali - Prakosa, Redo Mandra (Journal of Tourism and Creativity, 2023)
Indonesian people is a society that literate with the digitalization. Sticking with the advance of information and communication technology, the society have entered the third wave where everything will live completely connected to the internet. The Godevi’s platform is the example one that contains information about tourism and history about village tourism, distance traveled, facilities, information about something to see, to do and to buy in the village tourism. The paper uses a literature study in the form of previous research that is still relevant with its research, the theoretical basis and concepts obtained from books, journals ana articles that are relevant with the paper. The implementation of information technology or digitalization in form of an booking and payment online system for object and products of village tourism in Bali that intended to facilitate tourist transactions when they want to visit village tourism that available on the Godevi’s platform or website.